2022
DOI: 10.3390/molecules28010157
|View full text |Cite
|
Sign up to set email alerts
|

MS/MS-Based Molecular Networking: An Efficient Approach for Natural Products Dereplication

Abstract: Natural products (NPs) have historically played a primary role in the discovery of small-molecule drugs. However, due to the advent of other methodologies and the drawbacks of NPs, the pharmaceutical industry has largely declined in interest regarding the screening of new drugs from NPs since 2000. There are many technical bottlenecks to quickly obtaining new bioactive NPs on a large scale, which has made NP-based drug discovery very time-consuming, and the first thorny problem faced by researchers is how to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…Incorporation of MS-based dereplication methods into the bioactivity guided process could be useful to ensure a more accurate and efficient discovery of novel RiPPs. [181][182][183][184][185][186] The expanding wealth of knowledge regarding RiPP biosynthesis has propelled the genome mining strategy to an increasingly significant role in RiPP discovery. When specific details about a RiPP biosynthetic gene cluster are identified, the conserved and vital PTM enzymes within it can be utilized for comprehensive gene mining within the same RiPP family.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of MS-based dereplication methods into the bioactivity guided process could be useful to ensure a more accurate and efficient discovery of novel RiPPs. [181][182][183][184][185][186] The expanding wealth of knowledge regarding RiPP biosynthesis has propelled the genome mining strategy to an increasingly significant role in RiPP discovery. When specific details about a RiPP biosynthetic gene cluster are identified, the conserved and vital PTM enzymes within it can be utilized for comprehensive gene mining within the same RiPP family.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent this issue, artificial intelligence technology was developed in NPs research. MS/MS-based GNPS molecular networking can produce visual networks consisting of chemically associated compounds and enables the identification of known compounds, structural class, and analogs [ 44 ]. This study revealed that a combination of bioactivity evaluation with an MS/MS-based GNPS approach can allow us to prioritize various Prunus mume extracts in the early fractionation process and improve the accuracy of target compound prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Critically, while the literature reviewed for this work mentions the suitability of MNs for analysis by graph/network theory algorithms, such appli-cations have been limited to minimum path length queries. 4,17 In future works, we intend to further develop MHN functionality to facilitate a “network analysis tool suite”, prospectively easing the process by which data-informed (bio)chemical interpretations are made.…”
Section: Discussionmentioning
confidence: 99%